Successful multimodal treatment of stage IV lymphoepithelioma-like thymic carcinoma - Dominika Zielińska; Cezary Piwkowski; Piotr Gabryel; Wojciech Dyszkiewicz (Termedia Publishing House, 2022)
Primary thymic carcinomas are very rare tumors. Their incidence is estimated around 1 to 3 cases per 10 million inhabitants. In this group, lymphoepithelioma-like carcinoma occurs (LELC) in 5-32% and the prognosis of advanced cases is poor. A 17-year-old man was admitted to the hospital because of an enlarged right cervical lymph node. A computed tomography (CT) scan of the chest revealed an 8 cm tumor in the anterior mediastinum, with suspected left brachiocephalic vein infiltration (Figure 1). Besides the tumor in the mediastinum and metastasis in the right cervical lymph node (Figure 2), no other lesions with increased 18F-FDG uptake on positron emission tomography (PET)-CT were demonstrated. All other tests (laryngological examination, abdominal CT, blood tests including -FP and -HCG, bone marrow biopsy) were negative for cancer involvement. The right cervical lymph node was excised and the patient was diagnosed with thymic LELC.